2019
DOI: 10.1016/j.geoderma.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale soil mapping using multi-configuration EMI and supervised image classification

Abstract: Reliable and high-resolution subsurface characterization beyond the field scale is of great interest for precision agriculture and agro-ecological modelling because the shallow soil (~1-2 m depth) is responsible for the storage of moisture and nutrients that are accessible to crops. This can potentially be achieved with a combination of direct sampling and Electromagnetic Induction (EMI) measurements, which have shown great potential for soil characterization due to their noninvasive nature and high mobility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 50 publications
0
82
0
Order By: Relevance
“…The dominant reference soil groups are Cambisols, Luvisols, Planosols, and Stagnosols (WRB, 2015). Previous research in this area showed that crop performance during long periods of water scarcity is strongly influenced by soil heterogeneity at the field scale and beyond (Brogi et al, 2019;Rudolph et al, 2015;Stadler et al, 2015;von Hebel et al, 2018). The study area is part of the Terrestrial Environmental Observatories (TERENO) network (Bogena et al, 2018;Schmidt, Reichenau, Fiener, & Schneider, 2012;Simmer et al, 2015).…”
Section: Study Areamentioning
confidence: 99%
“…The dominant reference soil groups are Cambisols, Luvisols, Planosols, and Stagnosols (WRB, 2015). Previous research in this area showed that crop performance during long periods of water scarcity is strongly influenced by soil heterogeneity at the field scale and beyond (Brogi et al, 2019;Rudolph et al, 2015;Stadler et al, 2015;von Hebel et al, 2018). The study area is part of the Terrestrial Environmental Observatories (TERENO) network (Bogena et al, 2018;Schmidt, Reichenau, Fiener, & Schneider, 2012;Simmer et al, 2015).…”
Section: Study Areamentioning
confidence: 99%
“…In precision agriculture, σ a patterns help to optimize fertilizer and irrigation application [6,7], to investigate long-term treatment effects [8], to investigate plant and soil interactions [9,10,11,12], and to test the ability of plants to grow in saline soil conditions [13]. The spatial distribution of σ a can also be used to identify buried cables [14], flood embankments [15], and features within morphological, geological, and geoarchaelogical units [16,17,18]. Recently, Heil et al [19] provided a comprehensive overview of σ a mapping applications focusing on the two-coil EM38 (Geonics Ltd., Mississauga, Canada) system.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases (2D and 3D models), the obtained data can be managed for calculating several parameters, such as water demand, detection of water deficit and indicators about solute transport of fertilizers in the plant [18]. Moreover, the images of the soil can be processed to obtain several parameters related to soil water management (such as soil moisture and detection of fertilizers) [19].…”
Section: Introductionmentioning
confidence: 99%